IN UTERO HAEMATOPOIETIC STEM CELL TRANSPLANTATION (IUHSCT) - Aurelio Maggio (Mediterranean Journal of Hematology and Infectious Diseases, 2009)
In utero haematopoietic stem cell transplantation (IUHSCT) is a non-myeloablative approach for the prenatal treatment of genetic disorders. However, in target disorders, where there is not a selective advantage for donor cells, a useful donor-cell chimerism has not been achieved There are three possible barriers to engraftment following IUHSCT : limited space in the fetus due to host-cell competition; the large number of donor cells needed, and the immunological asset of recipient . Animal models have shown different levels of resistance to IUHSCT engraftment. In primate, goat, rat and mouse the levels of engraftment that has been achieved were low and not therapeutic. Among 46 cases of IUHSCT reported in humans, successful engraftment was obtained only in cases of X-SCID. Useful levels of chimerism has not been achieved in non-immunodeficiency diseases, and a detectable engrafment , was reported only in one case of ß-thalassemia transplanted at 12 weeks of gestation by fetal liver cells In one <span style="color: black; font-family: Symbol; mso-ansi-language: EN-GB; mso-ascii-font-family: 'Times New Roman'; mso-hansi-font-family: 'Times New Roman'; mso-char-type: symbol; mso-symbol-font-family: Symbol;" lang="EN-GB">a-thalassemia case, where <span style="color: black; font-family: Symbol; mso-ansi-language: EN-GB; mso-ascii-font-family: 'Times New Roman'; mso-hansi-font-family: 'Times New Roman'; mso-char-type: symbol; mso-symbol-font-family: Symbol;" lang="EN-GB">a-globin-dependent hemoglobin production and anemia are present during fetal period, microchimerism and tolerance were suggested . To overcome the IUHSCT engraftment barriers , it is necessary to develop strategies to improve the competitive capacity of donor cells and to define the gestational age of the possible immunological “window of opportunity” in the human fetus. In utero haematopoietic stem cell transplantation (IUHSCT) is a non-myeloablative promising approach for the prenatal treatment of a variety of genetic disorders and could be an alternative option to therapeutical abortion in some congenital diseases like haematological hereditary syndromes.